2021
DOI: 10.1038/s41421-021-00329-3
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive investigations revealed consistent pathophysiological alterations after vaccination with COVID-19 vaccines

Abstract: Large-scale COVID-19 vaccinations are currently underway in many countries in response to the COVID-19 pandemic. Here, we report, besides generation of neutralizing antibodies, consistent alterations in hemoglobin A1c, serum sodium and potassium levels, coagulation profiles, and renal functions in healthy volunteers after vaccination with an inactivated SARS-CoV-2 vaccine. Similar changes had also been reported in COVID-19 patients, suggesting that vaccination mimicked an infection. Single-cell mRNA sequencing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
81
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(116 citation statements)
references
References 48 publications
(67 reference statements)
11
81
0
Order By: Relevance
“…However, there have been a few reported cases of surging blood cholesterol level after patients took on the COVID-19 vaccination. Liu et al (2021) confirmed the elevated blood cholesterol level after the first inoculation. Study by Tang et al (2021) found that abnormalities on blood cholesterol levels can indirectly increase the susceptibility of patients to the COVID-19 virus and increase risk of death due to the virus.…”
Section: Statement Of Problemssupporting
confidence: 53%
“…However, there have been a few reported cases of surging blood cholesterol level after patients took on the COVID-19 vaccination. Liu et al (2021) confirmed the elevated blood cholesterol level after the first inoculation. Study by Tang et al (2021) found that abnormalities on blood cholesterol levels can indirectly increase the susceptibility of patients to the COVID-19 virus and increase risk of death due to the virus.…”
Section: Statement Of Problemssupporting
confidence: 53%
“…Single cell RNA-seq (scRNA-seq) and CyTOF data of PBMC or whole blood from COVID-19 infection and SARS-CoV-2 mRNA vaccination reveals an increase of monocytes, B cells and CD4+ T cells 9,28-30 . To specifically assess distinct memory response induced by the heterologous and homologous vaccinations, we performed scRNA-seq and identified cell populations in PBMC.…”
Section: Resultsmentioning
confidence: 99%
“…Some evidence in this regard is provided by a detailed Chinese study on post-vaccination immune modulation. 15 Among other factors, young individuals <40 years of age, and females were observed to be at higher risk of acquiring COVID-19 with respect to comparators. Since majority of the participants in the present study were young health care workers, the age specific findings cannot be extrapolated to the general population.…”
Section: Discussionmentioning
confidence: 97%
“…Some evidence in this regard is provided by a detailed Chinese study on post-vaccination immune modulation. 15…”
Section: Discussionmentioning
confidence: 99%